The TALUBA Learning Model for Fostering Talu Ba (Baiman, Bauntung, Batuah) Character in Biology Learning - Ita Ita; Helpina Helpina (Universitas Islam Negeri Walisongo Semarang, 2026)
Character development remains a challenge in higher education science learning, which often emphasizes cognitive outcomes while neglecting affective aspects rooted in local wisdom. In biology education, learning models that systematically integrate authentic character values are still limited. This study examines the implementation of the TALUBA Learning Model, designed to develop Talu Ba (Baiman, Bauntung, Batuah) character in biology learning. Using a quantitative descriptive design, the study involved 28 students in a General Biology course in the Biology Education Department. Model implementation was observed through structured observation sheets across three meetings, while students’ Talu Ba character was measured using a validated self-assessment questionnaire. Results show that the TALUBA model was implemented very well by lecturers (M = 4.86) and students (M = 4.44) across its six learning steps. Students’ Talu Ba character also reached a very good category (M = 4.63). These findings indicate that the TALUBA model is highly practical and supports character development based on local wisdom in higher education biology learning.